Legal Review of the Evidence System in Handling the Criminal Act of Ordinary Theft - Manullang, Dasdo Parlindungan; Ismaidar, Ismaidar; Ramayanti, Ramayanti (Utan Kayu Publishing, 2025)
That theft is stated in Article 362 of the Criminal Code that